Dysautonomia: Recommendations from A to Z - Zar, Ronel M (Science Insights, 2024)
Dysautonomia is an intricate and sometimes misconstrued condition that impacts the autonomic nerve system, which is accountable for controlling involuntary biological functions such as heart rate, blood pressure, and digestion. This detailed analysis explores the diverse facets of dysautonomia, encompassing its etiology, manifestations, diagnostic procedures, therapeutic alternatives, and approaches to lifestyle management. We herein seek to provide a comprehensive overview of dysautonomia by examining recent research advancements and incorporating patient viewpoints. It intends to offer helpful information for persons who are coping with this complex disorder.